2014
DOI: 10.4314/ijbcs.v7i6.22
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between technological and nutritional meat quality parameters in local poultry populations (<i>Gallus gallus</i>) of Benin

Abstract: The current work aims at determining relationships between technological and nutritional meat quality parameters in Holli, Fulani, Sahoue, North and South indigenous chicken ecotypes of Benin. Color parameters (L*, a*, b*, hue and chroma), pH, texture, dry matter content, protein content, fat content, and ash content were collected on 52 cockerels of each ecotype slaughtered at 24 weeks old. In Holli chickens, dry matter content was highly and positively correlated with protein content (P<0.001; r = 0.57), mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…The aforementioned variables (fat and ash) showed negative correlations with moisture (−0.375 and −0.498, respectively), which is supported by literature ( 144 , 147 , 148 ), which could be attached to the fact that greater fatty muscles repulse moisture due to their low solubility ( 147 ). Fat was also found to be negatively associated with protein (−0.460), which is reinforced by previous authors ( 149 ). Moreover, muscle type ( 146 ) and rearing system ( 7 ) should be considered among those variables influencing meat composition.…”
Section: Discussionsupporting
confidence: 82%
“…The aforementioned variables (fat and ash) showed negative correlations with moisture (−0.375 and −0.498, respectively), which is supported by literature ( 144 , 147 , 148 ), which could be attached to the fact that greater fatty muscles repulse moisture due to their low solubility ( 147 ). Fat was also found to be negatively associated with protein (−0.460), which is reinforced by previous authors ( 149 ). Moreover, muscle type ( 146 ) and rearing system ( 7 ) should be considered among those variables influencing meat composition.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Adomeh (2018) showed that grilled chicken meat with the semi-spherical drum kiln was of better quality (low water content, high protein content, fiber and ether extract) compared to other types of grills used namely, the perforated clay pot, drum with upper lid cutoff cover and drum with both lids sealed. Moreoer, Tougan et al (2013) showed the existence of relationships between the technological and nutritional quality of chicken meat according to the ecotype in Benin. Our study revealed three devices for grilling chicken meat.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, CP was negatively correlated with CF (r0.53) (P0.05). In Holli chickens, dry matter content was positively correlated with protein and ash contents, and fat content was positively correlated with the meat texture, pH values and a*, but negatively correlated with the protein content (Tougan et al, 2013).…”
Section: Analysis Of Correlationsmentioning
confidence: 92%